2016
DOI: 10.1186/s40345-016-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mania associated with cessation of breastfeeding

Abstract: BackgroundThis case chronicles the unique presentation of psychotic mixed mania in a female 5 months after parturition and 1 week following breastfeeding discontinuation, highlighting a rarely recognized mania risk factor that is temporally delayed from parturition: breastfeeding discontinuation.Case presentationA 25-year-old G1P1 female with a past psychiatric history of a depressive episode in adolescence presented to the Emergency Department with her 5-month-old daughter, fiancée, and family 1 week after br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…The symptoms resolved quickly following treatment with lithium and olanzapine, and the patient was discharged from hospital 5 days later. There are distinct differences between this case and the case described by Schmidt et al (2016), such as the presence of substance abuse with Schmidt et al's patient. However, there are some definite similarities between the two cases, including maternal family histories of bipolar disorder, onset of mood episodes during adolescence, and breastfeeding/weaning female infants.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…The symptoms resolved quickly following treatment with lithium and olanzapine, and the patient was discharged from hospital 5 days later. There are distinct differences between this case and the case described by Schmidt et al (2016), such as the presence of substance abuse with Schmidt et al's patient. However, there are some definite similarities between the two cases, including maternal family histories of bipolar disorder, onset of mood episodes during adolescence, and breastfeeding/weaning female infants.…”
Section: Discussioncontrasting
confidence: 54%
“…There was no previous history of psychiatric illness, but the patient had a depressive episode following the first manic episode that remitted spontaneously 4 or 5 months later. Recently, Schmidt et al (2016) reported the case of a primiparous woman with a past history of depression who had first onset of a mixed episode 1 week after the cessation of breastfeeding. The symptoms resolved quickly following treatment with lithium and olanzapine, and the patient was discharged from hospital 5 days later.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of breastfeeding, there is a reversal control of dopamine tonic inhibitors [50], [51]. In breastfeeding mothers with a history of depression in adolescence when high dopamine levels trigger symptoms of manic depression and psychosis [52]. Mothers with a history of depression who weaned prematurely were more likely to have a more severe depressive disorder.…”
Section: Discussionmentioning
confidence: 99%